Implementasi Interpolasi Spline Untuk Meningkatkan Kualitas Skala Zooming Pada Citra Screen Capture CCTV - Juliati Juliati (Journal of Computer System and Informatics (JoSYC), 2020)
Various types of image processing that can be done by computers such as, improving the quality of the zooming scale on CCTV screen capture images (image processing) is one of the fields that is quite popular until now. An image can experience interference in the form of damage to some parts or pixels in the storage process, this damage is in the form of major errors in an image for example in an image resulting in increasing the quality of the zooming scale. In the settlement, the writer uses spline interpolation method which is a good method for estimating low and high values ​​that are not found in the sample data. Screen capture functions to tell others about what is seen on the screen of the attached device because sometimes it is able to explain a situation very accurately. Screen capture is often used for various tutorials to make it easier for readers to read and some use it to explain a situation to others if there is a problem with the device being used in order to get a solution. The design that is done later can improve the quality of the zooming scale on the cctv screen capture image and make it easier to analyze the image to be zoomed in and produce a better image.